Real-time reverse transcription recombinase polymerase amplification for rapid detection of murine hepatitis virus - Wang, Xiao; Sui, Xin; Ma, Yueyu; Li, Ming; Zhang, Xu; Fei, Dongliang; Ma, Mingxiao (Frontiers in Microbiology, 2022)
Murine hepatitis virus (MHV) is a highly infectious murine coronavirus that has a high potential for causing harm to host animals. This study aimed to develop a real-time reverse transcription recombinase polymerase amplification (RT-RPA) method for rapid detection of MHV in laboratory mice. Methods Specific primers and probes for RT-RPA assay were designed targeting the conserved region in the M gene of the MHV reference strain (accession no. FJ6647223) according to the TwistDx manual instructions. The specificity, sensitivity, and reproducibility of the RT-RPA method were evaluated and compared with those of the standard RT-qPCR method. The clinical applicability of this assay was evaluated using 68 field samples. Results Amplification using the newly developed RT-RPA assay was completed within 20 min at 37°C, while that using the RT-qPCR method required nearly 60 min. The RT-RPA method exhibited an obvious time-saving advantage. Both RT-RPA and RT-PCR methods had the same limit of detection, which was 4.45 × 101 copies/μL. The specificity was indicated by a lack of cross-reaction with MHV, pneumonia virus of mice, Sendai virus, hantavirus, minute virus of mice, and reovirus type III. The MHV detection rate of RT-RPA assays was 13.63% (9/66) and RT-qPCR assays was 15.15% (10/66). Cohen’s “kappa” (κ) analysis results exhibited a very good agreement between two methods with the value of κ ≥ 0.750(since κ = 0.939) and p < 0.0005 (since p = 0.000). Conclusion The RT-RPA assay offers an alternative tool for simple, rapid, and reliable detection of MHV in laboratory mice and has significant potential for application in laboratories.